Thiocolchicoside ameliorated glycation via lysine blockade and carbonyl entrapment - Khatian, Najeeb; Fayyaz, Talha; Ahmed, Hammad; Nisar, Uzair; Abid, Mohammad; Usman, Shumaila; Ali, Syed Abid; Abbas, Ghulam (Penerbit Universiti Kebangsaan Malaysia, 2025)
The phenomenon of glycation leads to formation of AGE, which plays central role in various health hazards and accelerates the aging process. The re-purposing approach provide rapid means to introducing potential leads to drug discovery program. Keeping this into account, the present study investigates thiocolchicoside, for its capacity to be repurposed as anti-glycation agent. To assess the anti-glycation potential, thiocolchicoside was selected on the basis SAR, it is a muscle relaxant which is synthetic derivative of colchicoside, thiocolchicoside at 0.5, 1 and 2 mM were used and tested on various assays such as AGE inhibition assay (intrinsic fluorescence), fructosamine adduct formation (NBT assay) and availability of free lysine by using TNBSA followed by Lysine blockade assay (OPA and molecular docking study). The structural changes in the BSA protein was determined by using the thioflavin-T and Congo red assays. Finally, the carbonyl entrapment assay also performed to confirm the mechanism of the anti-glycation action. Thiocolchicoside significantly reduced the AGEs production in BSA-fructose model with an IC50 value of 0.25 mM. The fructosamine adducts were found to be reduced along with enhanced availability of free lysine. Furthermore, it exhibited lysine blockade activity which was also validated by computational study. Thiocolchicoside also prevented the alteration in glycation mediated BSA conformation. Furthermore, it was also found to entrap carbonyl moieties. Thiocolchicoside has a showed the significant anti-glycation potential, which can be attributed to its ability to block lysine residue and entrap carbonyl compounds. Hence, this clinically used muscle relaxant present itself as a potential drug to be repurposed as anti-glycation agent.